(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: Conventional methods like Ziehl-Neelsen (ZN) staining and liquid culture have been the mainstay for diagnosis of Tuberculosis (TB). The gold standard Liquid Culture method has a longer turnaround time. In the wake of the TB catastrophe, newer rapid and easily accessible methods of detection are the need of the hour. A molecular method like the Xpert MTB/RIF assay has revolutionized the early and rapid diagnosis of TB. Objective of the current study was to assess the performance and utility of Xpert MTB/RIF assay for the diagnosis of M. tuberculosis in pulmonary and extra-pulmonary clinical specimens in a large Indian reference laboratory. Methodology: The reference methods used were MGIT Liquid Culture system and ZN smear microscopy. Our study was performed in Global Reference Laboratory, Metropolis Healthcare, Mumbai, India for a period of 18 months with consecutive one thousand and forty two (518 Pulmonary + 524 extra-pulmonaryspecimens) clinical specimens obtained from the patients with clinical suspicion of tuberculosis. Diagnostic performance (sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the three methods were calculated with standard formulae. Results: In comparison to MGIT Liquid culture, sensitivity of Xpert MTB/RIF assay for pulmonary and extra pulmonary specimens were 87.18% and 68.92%, respectively while in comparison to ZN smear microscopy the sensitivity of Xpert MTB/RIF assay for pulmonary and extra pulmonary specimens were 92.67% and 83.81%, respectively. Conclusion: Our study concludes that in combination with the MGIT culture, Xpert MTB/RIF assay will significantly improve the detection rate of MTB bacteria. SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), page: 7-13